1970
DOI: 10.3329/bjar.v34i1.5753
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping of hybrid maize with short duration vegetables at hill valleys of Bandarban

Abstract: The experiment was conducted at farmer’s field in Bandarban sadar areas daring rabi season 2004-05 and 2005-06 to find out the feasibility and profitability of growing short duration vegetables i.e., Potato (var. Heera,), lalsak (var. Red king,), spinach (var. local), and French bean (var. BARI Jharseem-2) with hybrid maize (var. Pacfic-11). The grain yield of sole maize was 9.65 t/ha whereas yield reduction was found in intercrop situation The maize equivalent yield showed that maize + spinach produced signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…The highest grain yield (9.47 t ha -1 in 2014-15 and 9.24 t ha -1 in 2015-16) was obtained from sole maize might be due to higher single cob weight and 1000-grain weight. Similar results were also reported by Uddin et al, 2009. Among the intercropped combinations, the maximum grain yield (9.01 t ha -1 in 2014-15 and 8.3 t ha -1 gm in 2015-16) of maize was recorded when it was grown as paired row (100%) + 1 row squash (40%) due to less inter specific competition.…”
Section: Resultssupporting
confidence: 87%
“…The highest grain yield (9.47 t ha -1 in 2014-15 and 9.24 t ha -1 in 2015-16) was obtained from sole maize might be due to higher single cob weight and 1000-grain weight. Similar results were also reported by Uddin et al, 2009. Among the intercropped combinations, the maximum grain yield (9.01 t ha -1 in 2014-15 and 8.3 t ha -1 gm in 2015-16) of maize was recorded when it was grown as paired row (100%) + 1 row squash (40%) due to less inter specific competition.…”
Section: Resultssupporting
confidence: 87%
“…Economic yields of the component crops were converted to wheat-grain-equivalent yield (WGEY), taking into account the prevailing minimum support price/market prices of the crops (Uddin et al, 2009). System productivity was calculated by adding the WGEY of the component crops.…”
Section: Methodsmentioning
confidence: 99%
“…Greater productivity obtained from pumpkin including the spinach system in both years might be due to the highest yield of spinach as compared to other leafy vegetables. Uddin et al (2009) also reported the greater system productivity in the maize + spinach intercropping system.…”
Section: System Productivitymentioning
confidence: 85%